Entre pétrole et tourisme, la conservation participative des patrimoines locaux au Timor-Leste (Timor oriental) - Dominique Guillaud; Laure Emperaire; Brunna Crespi; Rosalia Soares; Amandine Pequignot; Jean-Christophe Galipaud (Revue d'ethnoécologie)
Timor-Leste, a young country with a rich cultural diversity, is betting for its future on the development of heavy infrastructure. Its cultural policies are also under construction; presently, they focus on the promotion of conventional objects that are emblematic of the cultural diversity perceived at a national level. However, local populations have their own heritage that they have created, transmitted and updated, and which is hardly ever taken into account. We propose a reflection on the nature of this local heritage (territory, biodiversity, sacred objects, sacred places, narratives of origin, etc.), and on the way it has always incorporated a certain modernity. This reflection is derived from two field studies: the south coast with an oil project and a small island off the northern coast, targeted by tourism. The objectives of the research group are to build a collaborative process in order to identify and develop this heritage, while considering the diversity of the actors involved. They also aim at analyzing the strengths and limitations of such participatory approaches; although favoring the dialogue between research, populations and public policies, these approaches do not always account for the diversity of heritage objects and of holders of knowledge, and may reveal situations of tension in the land system. Our analysis shows that participatory mapping can only be one instrument among others in collaborative methodologies.